Indigenous America in the Spanish Language Classroom - Fountain, Anne, 1946- (Book collections on Project MUSE., 2023)
"Many Spanish language teachers have little understanding of the indigenous languages and cultures that are part of the Spanish-speaking Americas. This book proposes to fill that gap and help teachers include the history and culture of Indigenous Peoples using a social justice lens. Indigenous America begins with an overview of the history of colonialism throughout the Spanish-speaking Americas and ties it to language teaching curricula and standards. Each substantive chapter ends with a list of conclusions, a list of questions for discussion and debate, and a set of teaching topics and concrete classroom exercises. Fountain will include photographs of places, people, and artifacts to make this history tangible. Appendices with more details about incorporating some rich resources into the Spanish language classroom are included, as is a glossary of important terms. This book is the first resource of its kind and is timely--teachers are eager to include more voices in their courses"--